INTEGRATION OF FORMAL EDUCATION AND ISLAMIC BOARDING SCHOOLS AS NEW PARADIGM FROM INDONESIAN PERSPECTIVE - Hosaini, Hosaini; Rif’ah, Rif’ah; Muslimin, Muslimin (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
Islamic boarding schools are typical Indonesian educational institutions that adhere to various correlative learning systems between formal and non-formal. Problems that often occur are related to learning practices that require integration between the learning system at school and the learning system implemented at Islamic boarding schools. This research aims to describe the character-based Islamic education learning system which is one of the goals of national education in order to create a baldatun thayyibatun wa rabbun ghafur country. One effort to achieve this goal is the educational process in formal, non-formal and informal institutions which is directed not only at equipping students with textual knowledge. However, preparing students to become human beings who have a spirit of patriotism and nationalism for the nation is a necessity which is the main vision of this country. The approach used in this research is a literature study with a literature review type of research. The findings of this research explain that Islamic boarding schools are a form of non-formal education with an integrative learning system as the forerunner of a new paradigm and Indonesian perspective in achieving maximum educational and learning goals, namely an education system that is able to produce quality human resources so that they can contribute to country. This is while still being guided by Islamic teachings and values which are based on the Al-Quran and Hadith.